Multicenter Comparison Study of both Analytical and Clinical Performance across Four Roche Hepatitis C Virus RNA Assays Utilizing Different Platforms - Vermehren, Johannes (J Clin Microbiol, 2017)
The efficacy of antiviral treatment for chronic hepatitis C virus (HCV) infection is determined by measuring HCV RNA at specific time points throughout therapy using highly sensitive and accurate HCV RNA assays. This study compared the performances of two recently developed real-time PCR HCV RNA assays, cobas HCV for use on the cobas 6800/8800 systems (cobas 6800/8800 HCV) and cobas HCV for use on the cobas 4800 system (cobas 4800 HCV), with those of two established assays, the Cobas AmpliPrep/Cobas TaqMan HCV quantitative test, version 2 (CAP/CTM v2) and the Cobas TaqMan HCV test, version 2 for use with the High Pure system (HPS/CTM v2). The limits of detection (LODs) and linearity at lower concentrations (5 to 1000 IU/ml) were assessed for cobas 6800/8800 HCV and cobas 4800 HCV using WHO standard traceable panels representing HCV genotypes (GT) 1 to 4. Pairwise assay comparisons were also performed using 245 clinical samples representing HCV GT 1 to GT 4. Results from cobas 6800/8800 HCV and cobas 4800 HCV were linear at low HCV RNA concentrations (<0.3 log(10) IU/ml difference between expected and observed results) with LODs of 8.2 IU/ml and 11.7 IU/ml, respectively, for GT 1. The new assays showed excellent agreement with results from CAP/CTM v2 and HPS/CTM v2 in samples with quantifiable viral loads. The concordances using the 6 million IU/ml cutoff were high among all four assays (90 to 94%). In conclusion, the cobas 6800/8800 HCV and cobas 4800 HCV tests are sensitive and linear and correlate well with the established Roche assays used in clinical practice.